Republic of Mozambique : Second Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria; Staff Report; Debt Sustainability Analysis; Press Release; and Statement by the Executive Director for Republic of Mozambique. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Mozambique's Second Review Under the Policy Support Instrument (PSI) and Request for Modification of Assessment Criteria. Mozambique's economy remains buoyant and recovered quickly from the severe floods in early 2013. Growth is estimated at 7 percent for 2013, with strong performance in coal mining, construction, transport, communications, and financial services. Inflation remains low notwithstanding accommodative monetary policy and rapid credit expansion. The real effective exchange rate was broadly stable in 2013 and a nominal appreciation against the South African rand helped to limit inflation. Program performance to date has been broadly satisfactory. The IMF staff recommends the completion of the second PSI review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet